PENETAPAN KADAR AMILOSA DAN PROTEIN PADA BERAS SOLOK JENIS ANAK DARO DAN SOKAN YANG DITANAM DENGAN SISTEM PERTANIAN ORGANIK DAN SISTEM PERTANIAN KONVENSIONAL - Rini Lestari; Sri Kartini; Lusiana Berti; Megi Romita (JURNAL FARMASI DAN MAKANAN, 2018)
The organic farming system is a holistic agricultural production management system for improving and developing agro-ecosystem health, including biodiversity, biological cycles, and soil biological activities. Organic farming systems use natural fertilizers and pesticides, while conventional farming systems still use chemical fertilizers and pesticides. Environmental conditions are expected to affect the chemical content of rice. One of the main chemical constituents in rice is amylose and protein. This research is a laboratory experimental study that aims to see the amylose and protein content of Solok rice types sokan and anak daro which grown with organic farming system and conventional farming system. From the result of the research, equation of calibration curve amylose is Y = 0,0246X + 0,0146 with correlation coefficient (r) = 0,9984. Amylose content of Solok rice type of anak daro organic 28,90%, anak daro conventional 28,04%, sokan organic 30,32% and sokan conventional 30,94%. Protein content of Solok rice type of anak daro organic 8,79%, anak daro conventional 8,15%, sokan organic 8,50% and sokan conventional 8,25%. T value of each group is smaller than the T table value, it can be concluded that the result is not significantly different.